FILLED POLYMER COMPOSITES BASED ON MODIFIED POLYPROPYLENE - Abdukarimova S. A.; Yodgorov N. N.; Makhkamova L. K.; Yusupova G. B. (Galaxy International Interdisciplinary Research Journal, 2023)
Glass fibers (GF) are the reinforcement component most used in Polyamide (PA), polycarbonate(PС), polybutylene terephthalate (PBT) and polypropylene (PP) based composites, as they have good balance between mechanical properties and costs. Reinforced Polypropylene composites final properties are mainly determined by the strength and stability of the polymer- PP-g-MAH- glass fiber interphase. Glass fibers do not act as an effective reinforcing material when the PP-g-MAH concentration is low. The effect of process parameters on the mechanical properties of composite manufactured specimens is discussed based on the results of tensile tests, three-point flexural tests, Izod impact tests, heat distortion temperature and melt index.